Sustainable Business Innovation Strategies To Enhance Msme Competitiveness In The Digital Economy Era - Achmad Efendi; Siti Masruroh; Zainal fanani (International Journal of Economics, Science, and Education, 2025)
In the face of rapid digital transformation and heightened global competition, Micro, Small, and Medium Enterprises (MSMEs) are increasingly required to adopt sustainable innovation strategies to remain competitive. This study investigates the role of sustainability-oriented business innovation in enhancing the competitiveness of MSMEs in the digital economy. Using a mixed-method approach, both qualitative interviews and quantitative surveys were conducted among selected MSMEs in Indonesia. The findings reveal that MSMEs which integrate digital technologies, environmental responsibility, and market-driven innovation are more resilient and agile in responding to market dynamics. Furthermore, sustainability-oriented innovation positively influences operational efficiency, customer satisfaction, and long-term competitive advantage. These results are supported by previous research on the synergy between digital transformation and sustainable practices. The study offers practical implications for MSME policymakers and practitioners, emphasizing the need for integrated innovation frameworks and capacity building in digital and sustainability capabilities